The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/1319-2442.160199
|View full text |Cite
|
Sign up to set email alerts
|

Retained fragmented double J ureteric stent: A report of four cases with review of the literature

Abstract: Polyurethane double-J ureteral stents are widely used in the field of urology. Postoperatively, patient education about the ureteral stent and making sure it is removed at the prescribed time is an utmost necessity. Forgotten ureteral stent is not only disastrous for the patient but also fraught with serious medico-legal implications for the urologist. Herein, we present four cases of long-term retained part of ureteral stent with its varied presentation and subsequent management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In this study, we report for the first time on SSF, which occurred as early as 3 weeks following stent insertion. SSF is a very rare complication 4‐6,9 . Regardless of the exact cause of stent fragmentation, both in vivo and in vitro reports have indicated that stents are more likely to fragment across the side drainage holes 2,13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we report for the first time on SSF, which occurred as early as 3 weeks following stent insertion. SSF is a very rare complication 4‐6,9 . Regardless of the exact cause of stent fragmentation, both in vivo and in vitro reports have indicated that stents are more likely to fragment across the side drainage holes 2,13 …”
Section: Discussionmentioning
confidence: 99%
“…Aging of the stent has also been recognized as an important cause for stent fragmentation 10,14 . In this regard, reviewing the literature indicated that SSF had occurred in stents which have been neglected or forgotten for long periods ranging between one year to as long as 15 years which led to stent encrustations and crystal formation 4‐6,9 . There was only one report of SSF which occurred after two months of insertion 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lam et al analyzed 26 forgotten catheters and showed that it was necessary the use of 2.7 procedures to resolve the situation ( 9 ). Forgotten double J stents and their complications are not rare in literature ( 4 - 8 , 10 , 11 ) particularly in public health services and lower income patients, due to the difficulty to follow up this population that are unaware of the severity of the condition. Likewise, Divakaruni et al observed 16% of forgotten double J catheters in their retrospective cohort, and identified a higher risk group including males and patients without medical insurance (2.5 and 6 times more prone to this complication, respectively) ( 11 ).…”
mentioning
confidence: 99%